[Non-drug treatment of rheumatoid arthritis : An analysis of claims data and a survey of insured persons (Project PROCLAIR)] - Jacobs, H.; Callhoff, J.; Hoffmann, F.; Zink, A.; Albrecht, K. (Z Rheumatol, 2019)
BACKGROUND: Only small amounts of data are available on the prescription frequency of physical therapies (PT) for patients with rheumatoid arthritis (RA). OBJECTIVE: The aim of the study was to evaluate prescription frequencies of PT considering functional status and sociodemographic factors. MATERIAL AND METHODS: A total of 98,963 adults diagnosed with RA in 2013 were identified in claims data from the BARMER health insurance. A questionnaire was sent to a representative sample of 6193 people requesting information on the disease status. Of these 2535 persons were included who agreed to the linking of the questionnaire and claims data and who confirmed a diagnosis of RA. From the routine claims data the prescription of PT and occupational therapy as well as the medical discipline of the prescribing physician were analyzed. Multivariable logistic regression was conducted to determine which variables (age, sex, M05/M06 diagnosis, residential area, income, functional status and rheumatological care) were associated with the use of PT. RESULTS: In 2015 a total of 47% of the study population received PT (35% physiotherapy, 15% thermotherapy, 15% manual therapy, 2% electrotherapy and 6% massage) and 3% occupational therapy. Of the PT prescriptions 37% were issued by general practitioners, 27% by orthopedists and 18% by rheumatologists. Women and persons living in the eastern states of Germany and patients with high functional impairment were prescribed PT more often. Income, educational status, seropositivity and rheumatological care did not have any influence on the frequency of prescription of PT. CONCLUSION: There are deficits in the outpatient prescription of PT but without indications of an undersupply of population groups due to low socioeconomic status. In contrast to the prescription of disease-modifying antirheumatic drug (DMARD) treatment, PT is predominantly prescribed by general practitioners.